Tikhonov type regularization methods for inverse mixed variational inequalities. (1st February 2020) - Chen, Jiawei; Ju, Xingxing; Köbis, Elisabeth; Liou, Yeong-Cheng
Abstract : In this paper, we focus on a Tikhonov type regularization method for inverse mixed variational inequalities. Existence of solutions of the inverse mixed variational inequalities and its regularized problem are established. We also present the relationships among three coercivity conditions for inverse mixed variational inequalities. Finally, the nonemptiness and boundedness for the solutions set of the regularized problem are derived under some mild conditions.